Deltora quest. Volume 1 - Niwano, Makoto, 1964-; Braff, Michael; Kobayashi, Mayumi; Rodda, Emily (New York : Kodansha Comics, 2011)
When Endon, the young son of the King and Queen of Deltora, inherits the throne and the magical Belt of Deltora after his parents' mysterious deaths, his best friend Jarred discovers a plot to strike at the throne from within. Before he can alert his new king of the danger, Jarred is framed for murder and forced to run for his life, but that will not prevent him from defending his king and his country.
"A Kodansha Comics trade paperback original"--T.p. verso.
"First published in Japan in 2005 by Kodansha, Ltd., Tokyo"--T.p. verso.
"T Ages 13+"--Cover p. [4].
Translated from the Japanese.
Translation of: Derutora kuesuto.
Adult.
Keywords: Rodda, Emily -- Adaptations; Rodda, Emily -- Adaptations; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Orphans -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Manga; Orphans -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels